Assessment of Activity-Based Instruction in Overcoming 7th Grade Middle School Students’ Misconceptions in Algebra - Özge Erdem, Gülfem Sarpkaya Aktaş (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
In this study, it is purposed to determine the effectiveness of proper atmosphere for learning in overcoming misconceptions and the difficulties that the students in 7th grade encounter while learning Algebra. In this paper, researcher-teacher model was used, and the study was supported with mixed method that ties between qualitative and quantitative researches. A concept test (CT) with 26 questions was developed about determining misconceptions and conceptual understanding of the students in the field of Algebra. The population of the study consists of 54 students in a middle school in a district of Van city in 2016-2017 education year. In qualitative part of the study, empirical research method was used. 14 activities were performed on experimental group for 3 weeks. The concept tests which are also used as pre-test and post-test was assessed by using 8 rubrics. In the quantitative part of the study, the findings were designed by making unstructured interview with 12 students chosen from the control and experimental groups. The findings obtained showed that activity-based learning was more effective in overcoming misconceptions. The misconceptions the students have generally focused on the factors such as they couldn’t understand different usage of the letters in algebra, they believed the letters should be made up only by numbers, they thought each letter has only one value and the expressions like ab are two digit numbers.